Analisis Kelayakan Video Pembelajaran Berbasisi Platform Youtube Melalui Pembelajaran Ips Di Sd - Safa, Libie Siti (Universitas Pendidikan Indonesia Kampus Serang, 2022)
The purpose of this study is to analyze educational video content on the YouTube platform. This study aims to examine and describe educational video content on the Natural Resources YouTube platform. The YouTube platform is often used as a source for uploading educational content in the form of learning videos and also learning videos that are still on the YouTube platform are often used as a teacher's learning media, but the learning content on videos has not been demonstrated. be possible. To assess the reliability of learning films, it is necessary to analyze learning videos on the YouTube platform, using a qualitative approach using content analysis research methods. In particular, data collection is carried out through the YouTube platform using the key term